Risk Factors for Multidrug Resistant organisms in Exacerbation of COPD (Chest & Heart Journal, 2023)
Background & Objective: Bacterial infections are the major cause of acute exacerbation of COPD (AE-COPD). The natural history of chronic obstructive pulmonary disease is characterized by frequent exacerbations. Majority of exacerbations are infectious and bacteria responsible for 30-50% of these cases. Appropriate use of antibiotic reduce mortality, hospital stay, subsequent exacerbations, further lung damage and also prevention of development of antibiotic resistance.Patients & Methods: This cross sectional observational and analytical study conducted at the Department of Respiratory Medicine in National Institute of Diseases of the Chest and Hospital from July 2019 – June 2020. A total of 102 patients with acute exacerbation of COPD were enrolled in this study. Early morning Sputum were examined for bacteriological culture and sensitivity. Multidrug-resistance was determined according to European Centre of Disease Prevention and Control classification.Result: One hundred and two exacerbations were included and microorganisms were isolated in 50 cases. Pseudomonas aeruginosa15(30%),Klebsiella pneumoniae14(28.0%) and Acinetobacter 11(22%) were more frequent. Multidrug-resistant pathogens were found in 35(70%) cases. In multivariateanalysis,preevious hospitalization (Odds ratio2.19,95% CI 1.22-3.91), frequent antibioticuse (OR 3.136, 95% CI 1.37-7.15) and chronic kidney disease (7.560,95%CI 1.82-31.33) were found to be independent predictors for MDR pathogens. Irregular use of antibiotics (p